2022
DOI: 10.1007/s11191-022-00393-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Roles of Mathematics in Physics

Abstract: Modelling roles of mathematics in physics has proved to be a difficult task, with previous models of the interplay between the two disciplines mainly focusing on mathematical modelling and problem solving. However, to convey a realistic view of physics as a field of science to our students, we need to do more than train them to become fluent in modelling and problem solving. In this article, we present a new characterisation of the roles mathematics plays in physics and physics education, taking as a premise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is because mathematics is closely related to physics. This is in line with the results of the research from Palmgren & Rasa (2022), which showed that mathematics has an important and even inseparable role in physics and also in physics education. They add an explanation that mathematics is closely related to the formation of physics knowledge and that the role of mathematics cannot be separated from learning physics.…”
Section: Nature Identity: Kinesthetic Learning Style and Love Of Math...supporting
confidence: 90%
“…This is because mathematics is closely related to physics. This is in line with the results of the research from Palmgren & Rasa (2022), which showed that mathematics has an important and even inseparable role in physics and also in physics education. They add an explanation that mathematics is closely related to the formation of physics knowledge and that the role of mathematics cannot be separated from learning physics.…”
Section: Nature Identity: Kinesthetic Learning Style and Love Of Math...supporting
confidence: 90%
“…Over the past two decades, there has been a remarkable growth in the body of literature exploring the role of mathematics in scientific disciplines. Much of this work has focused on its role in physics education (Pospiech et al, 2019;Palmgren and Rasa, 2022). While traditionally, mathematics has been regarded primarily as a tool in physics, its role has lately been recognised to extend beyond these conventional notions, suggesting a twofold nature (Uhden et al, 2012).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…It is also necessary for teachers to master additional pedagogical knowledge about modelling [ 19 ]. The opportunities and forms of MM embedded in teaching are flexible, appearing in various learning stages [ [20] , [21] , [22] ], in different disciplines [ 23 , 24 ], with multiple carriers [ 25 , 26 ], and combined with other strategies [ 27 , 28 ]. To present the panorama of MMER, we included science education research related to modelling practice into the scope of analysis and tried to obtain the international hot spots and trends.…”
Section: Introductionmentioning
confidence: 99%